2007
DOI: 10.1007/s00330-007-0647-5
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of contrast-enhanced cine-MR sequences in the assessment of left ventricular function: comparison with precontrast cine-MR sequences. Results of a bicentric study

Abstract: The accuracy of contrast-enhanced cine magnetic resonance (cine-MR) imaging to determine left ventricular function was assessed by comparison with the established noncontrast cine-MR sequences. Contrast-enhanced balanced steady-state free precession (cine-SSFP) sequences were compared with precontrast cine-SSFP sequences in the assessment of left ventricular contractile function in 30 consecutive patients with various cardiac diseases. Five to eight short-axis image sections were obtained in each patient. Quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…This proportion is higher than the 44% sensitivity reported by Abdel-Aty et al [14] for spin-echo T1-weighted sequences and the 52% report- [2] for late gadoliniumenhanced sequences but is in agreement with the 88% sensitivity reported by Mahrholdt et al [15] for gradient-echo inversion recovery T1-weighted sequences. The locations of abnormalities, predominantly in the epicardial portion of the lateral free wall, are also in agreement with those in previous studies [13,16,17]. One additional case of subepicardial areas of high signal intensity suggestive of lesions of acute myocarditis was detected on contrast-enhanced cine images but not identified as such on late gadolinium-enhanced images.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This proportion is higher than the 44% sensitivity reported by Abdel-Aty et al [14] for spin-echo T1-weighted sequences and the 52% report- [2] for late gadoliniumenhanced sequences but is in agreement with the 88% sensitivity reported by Mahrholdt et al [15] for gradient-echo inversion recovery T1-weighted sequences. The locations of abnormalities, predominantly in the epicardial portion of the lateral free wall, are also in agreement with those in previous studies [13,16,17]. One additional case of subepicardial areas of high signal intensity suggestive of lesions of acute myocarditis was detected on contrast-enhanced cine images but not identified as such on late gadolinium-enhanced images.…”
Section: Discussionsupporting
confidence: 91%
“…In the detection and loca-tion of lesions of myocardial infarction, Laissy et al [5] found good correlation between late gadolinium-enhanced and contrast-enhanced cine images. Another advantage is that contrast injection does not preclude measurement of left ventricular function on contrast-enhanced cine images [13].…”
Section: Discussionmentioning
confidence: 99%
“…The observed non-significant differences between functional parameters acquired in CT and MRI [17,18] may be caused by physiological effects due to rapid contrast material injection and the absence of beta-blocker medication in CT. In summary, a sufficient evaluation of the left ventricular function and wall motion is feasible with CT angiography datasets acquired for the examination of the coronary arteries, thus adding a comprehensive functional aspect to the static morphological assessment in CT and possibly rendering the modality a one-stop shop similar to MRI for some indications [6].…”
Section: Discussionmentioning
confidence: 82%
“…These results indicate that contrast enhancement does not prevent cine imaging assessment using the SSFP sequence. 15 ceSSFP may allow observation of both myocardial injuries and LVOT obstruction after ASA in a single scan. Because we performed ceSSFP during the interval between gadolinium injection and Look-Locker T 1 scout imaging, there was no penalty of examination time.…”
Section: Discussionmentioning
confidence: 99%